2021
DOI: 10.1002/jcad.12401
|View full text |Cite
|
Sign up to set email alerts
|

Managing threats: A grounded theory of counseling engagement in clients with experiential avoidance

Abstract: Constructivist grounded theory methods were used to explore counseling engagement in clients with strong tendencies to avoid aversive emotion. Participants initially viewed counseling as a potentially adversarial and harmful relationship. An expectation and fear of judgment, as well as shame and self-judgment, contributed to this view. Participants also reported anxiety about addressing specific issues. Their perceptions led to withholding of personal information and minimal engagement. The participants were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(64 reference statements)
0
0
0
Order By: Relevance
“…Among those reporting negative impacts (I−), several sources, both quantitative (Baumann & Hill, 2016; Hill et al, 1993) and qualitative (Blanchard & Farber, 2020; Farber et al, 2006; Tursi et al, 2022), identified in-session manifestations of shame as a common reason for nondisclosure. Moreover, shame also affected treatment outcome: Trait and trauma-related shame assessed during treatment were found to predict lower improvement in (Harned et al, 2020) and higher levels of (Øktedalen et al, 2015) PTSD symptoms, and lower improvement in suicidal and self-harming tendencies in BPD (Rizvi & Fitzpatrick, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Among those reporting negative impacts (I−), several sources, both quantitative (Baumann & Hill, 2016; Hill et al, 1993) and qualitative (Blanchard & Farber, 2020; Farber et al, 2006; Tursi et al, 2022), identified in-session manifestations of shame as a common reason for nondisclosure. Moreover, shame also affected treatment outcome: Trait and trauma-related shame assessed during treatment were found to predict lower improvement in (Harned et al, 2020) and higher levels of (Øktedalen et al, 2015) PTSD symptoms, and lower improvement in suicidal and self-harming tendencies in BPD (Rizvi & Fitzpatrick, 2021).…”
Section: Resultsmentioning
confidence: 99%